Zinc‐ion hybrid supercapacitors: Design strategies, challenges, and perspectives. Issue 2 (5th September 2022) - Chen, Xiudong; Zhang, Hang; Gao, Yun; Liu, Jin‐Hang; Cao, Xiaohua; Zhan, Changchao; Wang, Shitao; Wang, Jiazhao; Dou, Shi‐Xue; Cao, Dapeng
Abstract: Zinc‐ion hybrid supercapacitors (ZHSCs) may be the most promising energy storage device alternatives for portable and large‐scale electronic devices in the future, as they combine the benefits of both supercapacitors and zinc‐ion batteries. Even though many surprise outcomes have been accomplished with ZHSCs, the creation of suitable cathode materials and electrolytes, as well as the enhancement of zinc anodes, continue to be the most difficult obstacles in the development of high‐performance ZHSCs. The low capacitance of the cathode material, poor stability, and low utilization rate of the zinc anode seriously affect the electrochemical performance and application of ZHSCs. Furthermore, parasitic processes in aqueous electrolytes, such as the hydrogen and oxygen evolution reactions might result in low‐voltage windows and unsatisfied cycling performance of the ZHSCs. This review provides a concise summary of the most recent developments and energy storage mechanisms in ZHSCs. Meanwhile, the cathode material design strategy (structural engineering, hybrid‐composite design, heteroatom doping, and so on), the zinc anode design strategy (zinc foil improvement, zinc‐free metal composites, and so on), and the structure–activity relationship of the electrochemical performance of ZHSCs are discussed. Additionally, a summary of the impact of modifications in electrolyte composition on the electrochemical performance of ZHSCs is provided. Finally, this review also discusses the future development direction of ZHSCs. It is anticipated that this evaluation will serve as a helpful reference for the creation of high‐performance ZHSCs, which will hasten the development of these devices. Abstract : This review summarizes the latest progress, energy storage mechanisms, and current challenges in zinc‐ion hybrid supercapacitors (ZHSCs), based on the three aspects of cathode and anode material design strategy, and electrolyte optimization composition. This review provides a useful reference for the construction of high‐performance ZHSCs for speeding up their development.